Technical efficiency of chili production - A. S. M. Anwarul Huq,; Mohamed Arshad, Fatimah (Science Publications, 2010)
Scarcity of resources has led to production economists to think about the reallocation of existing resources to produce a prescribed level of output with the minimum cost without changing the production technology. But there is a lack of information about the efficient use of inputs in chili production. Except for a few descriptive studies, econometric analysis has yet to be conducted to examine the production function for chili cultivation and its potential for future improvement in Bangladesh. Approach: In this study an effort was made to assess the level of technical efficiency required for chili production in the administrative district of Jamalpur and also analyzed the status of resource allocation for its production. The Cobb-Douglas stochastic production frontier model was used to analyze the data. Results: The study revealed that cultivation of chili is highly profitable. The net return against cultivating of chili was Tk 73,164 ha-1 while the Benefit Cost Ratio (BCR) was 1.93. However, all the farmers were not very close to the maximum frontier outputs (efficiency levels varying from 11-96% and their mean efficiency was 77%). Conclusion: On an average, 23% technical inefficiency appears which implies that the output per farm can be increased on an average by 23% through chili production using the prevailing technology and without incurring any additional production cost. Side by side advanced technology (high yielding variety, disease and pest management) could be adapted to increase production of this particular spice.